2008
DOI: 10.1016/j.bmc.2008.01.025
|View full text |Cite
|
Sign up to set email alerts
|

DNA polymerase bypass in vitro and in E. coli of a C-nucleotide analogue of Fapy·dG

Abstract: Bypass of the configurationally stable analogue (β-C-Fapy•dG) of the formamidopyrimidine lesion derived from 2'-deoxyguanosine oxidation (Fapy•dG) was studied in vitro and in E. coli. The exonuclease deficient Klenow fragment of E. coli DNA polymerase I (Klenow exo¯) misincorporated dA most frequently opposite β-C-Fapy•dG, but its efficiency was <0.2% of dC insertion. Klenow exo¯ fidelity was enhanced by the enzyme's high selectivity for extending duplexes only when dC was opposite β-C-Fapy•dG. The expectation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…To dissect the differences between the α and β forms, several studies utilized stabilized analogs of Fapy‐dG. These investigations demonstrated that the β anomer preferred a dC as the pairing partner in duplex DNA and modestly inhibited DNA synthesis in vitro [Ober et al, ; Weledji et al, ; Büsch et al, ; Gehrke et al, ]. This was in contrast to the α anomer that strongly destabilized DNA structure regardless of the opposing nucleotide, and represented a nearly complete block to all DNA polymerases examined, including low‐fidelity Dpo4 and pol η [Büsch et al, ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To dissect the differences between the α and β forms, several studies utilized stabilized analogs of Fapy‐dG. These investigations demonstrated that the β anomer preferred a dC as the pairing partner in duplex DNA and modestly inhibited DNA synthesis in vitro [Ober et al, ; Weledji et al, ; Büsch et al, ; Gehrke et al, ]. This was in contrast to the α anomer that strongly destabilized DNA structure regardless of the opposing nucleotide, and represented a nearly complete block to all DNA polymerases examined, including low‐fidelity Dpo4 and pol η [Büsch et al, ].…”
Section: Resultsmentioning
confidence: 99%
“…Collectively, these data may suggest that the α anomer is a cytotoxic lesion, with no or only a minor role in mutagenesis, whereas the β anomer could be primarily responsible for Fapy‐dG‐induced mutations, particularly G → T transversions. However, a conformationally fixed analog of β‐Fapy‐dG was essentially nonmutagenic in E. coli [Weledji et al, ]. It is worth noting that the highest frequency of G → T transversions observed for native Fapy‐dG in E. coli was <2% [Patro et al, ].…”
Section: Resultsmentioning
confidence: 99%
“…Replication studies of Fapy-dGuo and its configurationally stable analogues have also been reported (43, 44). The mutagenicity of the Fapy-dGuo lesion was low in bacteria (55, 56); the mutagenic frequency of Fapy-dGuo was higher in mammalian cell lines and also found to be sequence dependent (55). The major mutation was Gua→Thy transversions in both systems.…”
Section: Discussionmentioning
confidence: 99%
“…These configurationally stable Fapy analogues are useful probes, particularly in templates for co-crystallization studies with base excision repair proteins, and are potentially useful as repair enzyme inhibitors. 2931 …”
Section: Synthesis Of Oligonucleotides Containing Formamidopyrimidmentioning
confidence: 99%